Utilizing Plant Growth-Promoting Rhizobacteria (PGPR) to Advance Sustainable Agriculture - Piao Yang; Abraham Condrich; Sean Scranton; Camina Hebner; Ling Lu; Muhammad Azam Ali (Bacteria)
Plant growth-promoting rhizobacteria (PGPR) are beneficial bacteria that play a crucial role in sustainable agriculture by enhancing plant growth through various mechanisms. This review examines the contributions of PGPR in improving nutrient availability, producing phytohormones, providing biocontrol against pathogens, and enhancing abiotic stress tolerance. By reducing the necessity for chemical fertilizers and pesticides, PGPR mitigate environmental impacts, enhance soil health, and support long-term agricultural productivity. However, challenges such as inconsistent performance across various soils, regulatory barriers, and limited farmer awareness, hinder their widespread adoption. Recent advancements in nano-encapsulation technology, genetic engineering, and bioinformatics, present promising solutions for overcoming these obstacles and enhancing PGPR efficacy. The incorporation of PGPR into biofertilizers, biopesticides, and integrated plant management (IPM) offers a sustainable resolution to global agricultural challenges. This review addresses the current state of PGPR research, applications, and future directions for optimizing their use in promoting sustainable agriculture.